Maladministration in the Public Service: Should Government Officials be Responsible for their Decisions? - Irmajayanti, Maulida Zulia; Sudaryanto, Totok; Antikowati, Antikowati (Advanced Studies on Socio-Economy Development, 2021)
The concept of the welfare state upholds the existence of the legal system under the premise of legal certainty and the protection of basic human rights. Paragraph IV of the 1945 Constitution of the Republic of Indonesia emphasizes the existence of â€œstate obligationsâ€ and â€œthe government dutyâ€ to protect and serve all public interest. The normative basis of the Constitution was translated as the national principle to embody the public services. The Public Service Law Number 25 of 2009 is a formulation of legal certainty. However, the main problem that occurs in the public services is maladministration in bureaucracy. It is important to build interpretations of the authority attached to the bureaucratic system or on subjects who become government officials. By analyzing the Constitution, this article states that the government official dimensions must be considered as an interrelated issue, so that the articulate practice must be seen as inherent social conditions. Keywords: Responsibility, Government Officials, Maladministration.